"Sermons are dangerous things": George Herbert, Richard Bernard, and the Politics of Preaching - Bell, Susan J. A. (Toronto journal of theology, 2010)
In early Stuart England the office and content of preaching were both important and controversial matters. In this time of the continuing reformation of the pastoral office, two manuals for pastors illustrate the ecclesiastical tension: George Herbert's Countrey Parson and Richard Bernard's Faithfull Shepheard. While the Calvinist Bernard and the conforming Herbert were both moderates and though their manuals show significant overlap, a comparison between the two works shows that Herbert developed a new and holistic understanding of the preaching office. Within his larger project of defending the English priesthood as a worthy profession, he situates the importance of the preached Word within the totality of the parson's ministerial duties. Moreover, the whole of pastoral presence and practice are seen as expressions of "sermon" and extensions of the preaching vocation.